Time-Compressed Speech Identification Is Predicted by Auditory Neural Processing, Perceptuomotor Speed, and Executive Functioning in Younger and Older Listeners - Dias, James W. (J Assoc Res Otolaryngol, 2018)
Older adults typically have difficulty identifying speech that is temporally distorted, such as reverberant, accented, time-compressed, or interrupted speech. These difficulties occur even when hearing thresholds fall within a normal range. Auditory neural processing speed, which we have previously found to predict auditory temporal processing (auditory gap detection), may interfere with the ability to recognize phonetic features as they rapidly unfold over time in spoken speech. Further, declines in perceptuomotor processing speed and executive functioning may interfere with the ability to track, access, and process information. The current investigation examined the extent to which age-related differences in time-compressed speech identification were predicted by auditory neural processing speed, perceptuomotor processing speed, and executive functioning. Groups of normal-hearing (up to 3000 Hz) younger and older adults identified 40, 50, and 60 % time-compressed sentences. Auditory neural processing speed was defined as the P1 and N1 latencies of click-induced auditory-evoked potentials. Perceptuomotor processing speed and executive functioning were measured behaviorally using the Connections Test. Compared to younger adults, older adults exhibited poorer time-compressed speech identification and slower perceptuomotor processing. Executive functioning, P1 latency, and N1 latency did not differ between age groups. Time-compressed speech identification was independently predicted by P1 latency, perceptuomotor processing speed, and executive functioning in younger and older listeners. Results of model testing suggested that declines in perceptuomotor processing speed mediated age-group differences in time-compressed speech identification. The current investigation joins a growing body of literature suggesting that the processing of temporally distorted speech is impacted by lower-level auditory neural processing and higher-level perceptuomotor and executive processes.